2006
DOI: 10.2166/wst.2006.344
|View full text |Cite
|
Sign up to set email alerts
|

Biological treatment of industrial wastes in a photobioreactor

Abstract: An algal-bacterial consortium was tested for the treatment from a coke factory. A Chlorella vulgaris strain and a phenol-degrading Alcaligenes sp. were first isolated from the wastewater treatment plant to serve as inocula in the subsequent biodegradation tests. Batch tests were then conducted with samples from the real wastewater or using a synthetic wastewater containing 325 mg phenol/l and 500 mg NH 4 þ /l as target pollutants. Direct biological treatment of the real wastewater was not possible due to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 11 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, the absence of significant methane and methanol degradation confirmed that microalgal activity is not capable of supporting the complete biodegradation of organic pollutants with very low CORS in the absence of bicarbonate. The results obtained by Tamer et al (2006) confirmed this hypothesis. These authors recorded an increase in the continuous degradation of phenol (CORS=−0.67) by a Chlorella vulgaris and Alcaligenes sp.…”
Section: Influence Of the Cors On Pollutant Degradationsupporting
confidence: 70%
“…Furthermore, the absence of significant methane and methanol degradation confirmed that microalgal activity is not capable of supporting the complete biodegradation of organic pollutants with very low CORS in the absence of bicarbonate. The results obtained by Tamer et al (2006) confirmed this hypothesis. These authors recorded an increase in the continuous degradation of phenol (CORS=−0.67) by a Chlorella vulgaris and Alcaligenes sp.…”
Section: Influence Of the Cors On Pollutant Degradationsupporting
confidence: 70%
“…10,52 This can be managed by using appropriate pretreatment technologies to remove sediment and to deactivate (sterilize) the wastewater. 53 …”
Section: Microalgal Farming Using Wastewatermentioning
confidence: 99%
“…Synthetic wastewater NH 4 -N -45 [108] C. vulgaris Azospirillum brasilense Synthetic wastewater P -31.5 N -22 [109] C. sorokiniana Activated sludge consortium Pretreated swine slurry N -94 -100 P -70 -90 [60] C. sorokiniana Activated sludge bacteria Piggery wastewater P -54 NH 4 + -N -21 [110] Chroococcus spp., Lyngbya spp.…”
Section: Algae-bacteria Associationmentioning
confidence: 99%